2020
DOI: 10.3389/fgene.2020.00996
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Drought-Responsive Transcriptome During Seed Germination in Adzuki Bean (Vigna angularis L.) by PacBio SMRT and Illumina Sequencing

Abstract: The full-length single-molecular sequencing and short reads Illumina sequencing were combined to generate the transcripts of adzuki bean with high-quality. A total of 17,636 loci and 60,454 transcripts were detected in this study. To characterize the drought-responsive genes during seed germination in adzuki bean, two varieties, i.e., tolerant and sensitive to drought stress, were selected to conduct analysis of alternative splicing dynamics (AS) and differentially expressed genes (DEGs) by combining the newly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…At the same time, DEGs with the same expression pattern were also enriched in amino acid metabolism, carbohydrate metabolism, signaling and cellular processes, ion channels, and other KEGG pathways, which suggests that there is an obvious co-regulatory system between NaCl and PEG induced osmotic response pathways. These findings are similar to those previously observed in Arabidopsis [ 44 ], alfalfa [ 1 ], rice [ 45 ], and red bean [ 13 ]. These results showed that when I. lactea var.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…At the same time, DEGs with the same expression pattern were also enriched in amino acid metabolism, carbohydrate metabolism, signaling and cellular processes, ion channels, and other KEGG pathways, which suggests that there is an obvious co-regulatory system between NaCl and PEG induced osmotic response pathways. These findings are similar to those previously observed in Arabidopsis [ 44 ], alfalfa [ 1 ], rice [ 45 ], and red bean [ 13 ]. These results showed that when I. lactea var.…”
Section: Discussionsupporting
confidence: 92%
“…chinensis under drought and salt stress. Moreover, due to the obvious disadvantages of second-generation sequencing, such as the short length of sequencing reads and unreliable assembly results, the accuracy of transcriptome abundance calculation is reduced to a large extent [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The application of long-read technologies to the exploration of the lncRNA repertoire in plants has been demonstrated for several plant species, including Oryza sativa L. ssp. japonica [ 27 ], Populus simonii [ 28 ], P. qiongdaoensis [ 29 ], poplar “Nanlin 895” [ 30 ], Trifolium pratense [ 31 ], Cardamine violifolia [ 32 ], and Vigna angularis [ 33 ]. These studies demonstrated that long-read sequencing can be used to obtain a comprehensive catalogue of lncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…The mass spectrometry data were transformed into MGF files with Proteome Discovery 1.2 (Thermo, Pittsburgh, PA, USA) and analyzed using Mascot search engine (Matrix Science, London, UK; version 2.3.2). Mascot database was set up for protein identification using Vigna angularis L reference genome 47 ( ftp://ftp.ncbi.nlm.nih.gov/genomes/all/GCF/001/190/045/GCF_001190045.1_Vigan1.1/ ), Vigna angularis L data in NCBI nr/Swiss-Prot/Uniprot/IPI database, and the PacBio SMRT and illumina sequencing data published by Zhu et al 18 . Mascot was searched with a fragment ion mass tolerance of 0.050 Da and a parent ion tolerance of 10.0 PPM.…”
Section: Methodsmentioning
confidence: 99%
“…Several bZIP genes were reported in response to drought and salt stress in Vigna radiata and V. angularis by whole-genome sequencing and quantitative real-time PCR analysis 17 . We previously selected a drought-tolerant variety and a drought-sensitive variety through the drought tolerance identification of adzuki bean seeds, and identified 82 differentially expressed genes (DEGs) in the germinating seeds between drought tolerant and drought sensitive variety of adzuki bean under drought stress by PacBio SMRT and Illumina Sequencing 18 . It provided a ideal materials for investigating protein expression patterns of two varieties under drought stress.…”
Section: Introductionmentioning
confidence: 99%